THE INTERDEPENDENCE AND MUTUAL INFLUENCE OF POLITICS AND ECONOMICS IN THE ERA OF GLOBALIZATION - Asian Anatolyevich Ozov (Современная наука и инновации, 2022)
In our era, the era of globalization, have become relevant concepts such as interaction, interdependence of politics and economics. It greatly and significantly changed the role of political parties and financial-industrial groups in the modern world, in international cooperation. Foreign economic relations play a very important role in the development of the regions and the country as a whole, ensuring that the reputation and image of Russia in the international arena. Today's international relations have a touch of economization. Transformed the mechanisms of interaction between international politics and Economics. An important problem in Russia is formulating its national interests in the conditions of economic globalization.